Physico-chemical properties of reconstituted fibers composite prepared from leather waste - VIJAYAN SUMATHI; RETHINAM SENTHIL (International Journal of Pharma and Bio Sciences, 2016)
The reconstituted fiber composite materials (RFCMs) were prepared by leather fibers (LF), Textile fibers (TF) viz., cotton fibers (CF)/polyester fibers (PF) and natural rubber latex (NRL).The objective of this composite material in boardformwas developed using finished leather waste (FLW), as a solid waste from the leather industry. Different concentrations of these natural polymers were used to find out the optimum concentration which gave better mechanical properties.RFCMswere characterized usingscanning electron microscopy (SEM) etc and biodegradation properties. Leather composites prepared using100 mL of natural rubber latex (NRL)possessed better mechanical properties viz., tensile strength, elongation at break (%), flexural strength, tearing strengthetc. Hence, the study focuses on the conversion of leather industry solid waste into value added products.